Malvinas Current Volume Transport at 41°S: A 24 Yearlong Time Series Consistent With Mooring Data From 3 Decades and Satellite Altimetry - Artana, Camila Indira (2018)
We combined altimetric data and the in situ data sets from three 10 years apart mooring deployments to compute a coherent and accurate volume transport time series of the Malvinas Current (MC) at 41°S. We used a method developed in Koenig et al. (2014) and explored three types of geostrophic shear to estimate the uncertainty derived from the lack of velocity data in the upper 300 m. The mean MC transport over 24 years in the upper 1,500 m is 37.1 ± 2.6 Sv and the standard deviation 6.6 ± 1 Sv. Since 1993, annual mean transports have varied from 32 to 41 Sv and the three in situ records corresponded to low annual mean transports. The MC transport time series is not stationary, its spectral content evolves with time showing significant energy at the 30–110 days, semiannual and annual period. The distribution of the MC volume transport anomalies is asymmetric, negatively skewed with larger negative anomalies than positive anomalies. Several transport maxima appear to result from cyclonic eddies that propagate northwestward following the 4,000–5,000 m isobaths and locally reinforce the circulation on the slope when they reach 41°S. During transport maxima, the northernmost extension of the Subantarctic Front (SAF) remains at its mean location (39.5°S). During minima, the SAF migrates southward of 41°S as positive anomalies shed by the Brazil Current overshoot moves westward onto the slope. Apart from continental trapped waves, changes in the MC volume transport at 41°S show no correlation with upstream conditions on the continental slope.